The effect of industrial practices on stream sediments, and the impact of these sediments on the geochemistry of a wetland - Lake, James Andrew (Department of Geological Sciences, 2016)
The objective of this study was to characterise the impact that a major industrial operation, situated at Somerset West and involved in the manufacturing of a diverse range of chemicals, has had on the sediments of the drainage system that drains the site on which these activities occur. Furthermore, the impact of these sediments on the geochemistry of a wetland, Wagenveldt vlei, situated downstream of the complex, has been investigated. Sediment cores and water samples were collected at a number of locations down the length of the drain . The water samples were analysed to determine which constituents were present in solution. The cores were separated into a top and bottom layer which were analysed separately to determine their geochemical composition. In some instances a lack of time resulted in some of the analyses being performed on only a select number of samples. An experiment was performed on the sediments collected from the bottom layer to determine what would happen if the sediments became oxic and the sulphides and organic matter in the sediments were oxidised.